Bridging the gap between Islam and the West: a reconciliation approach - Abdul Rahim, Adibah (International Institute for Muslim Unity, International Islamic University Malaysia, 2006)
Western influence on the Muslim world has been dominant since the beginning of the Nineteenth Century and it has colored human civilization and culture at the global level. In light of this phenomenon, it makes sense to ask the question; how did Muslims respond effectively, on an intellectual level, to the influence posed by the West. There have been various responses over the past century with different approaches. The two extremist groups could be characterized as those who advocated rejection of all the values of Western culture and civilization; and those who assimilated them blindly. Both are inadequate positions and are not able to present a real solution for the conflict between Islam and the West. Therefore, the response should be analyzed from the perspective of a third group which sought to bridge the gap between two civilizations, Islam and the West, and tried to develop a constructive relationship between the two. This paper tries to highlight the reconciliation approach of the third group to certain issues, namely, on the integration of religion and science and integration system of education.